Epidemiological and Clinical Characteristics of Hospitalized Pediatric Patients with SARS-CoV-2 Infection in Mexico City, Mexico. (25th April 2022) - Lugo-Zamudio, Gustavo Esteban; Aguilar-Rojas, Antonio; Vázquez-Medina, Martín Uriel; Gutiérrez-Ramírez, Antonio; Upton-Alvarado, Ma. Cristina; Espinoza-Rivas, Patricia; Lagunas-Torres, Gustavo; Rojo-Gutiérrez, María Isabel; Ibáñez-Cervantes, Gabriela; Vargas-De-León, Cruz
Abstract : Background . Evidence from across the world suggests that the pediatric population shows different clinical manifestations and has a lower risk of severe presentation of SARS-CoV-2 infection compared to adults. However, Mexico has one of the highest mortality rates in the pediatric population due to SARS-CoV-2 infection. Therefore, our objective was to explore the epidemiological and clinical characteristics associated with a positive confirmatory test in the Mexican pediatric population admitted to a tertiary care hospital in Mexico City. Methods . Clinical, imaging and laboratory data were retrospectively collected from 121 children hospitalized during the period from March 4 th, 2020, to August 8 th, 2021. The patients were identified as suspicious cases according to the guidelines of the General Directorate of Epidemiology of Mexico. Real-time polymerase chain reaction (RT-PCR) tests were used to confirm SARS-CoV-2 infection. Categorical variables were compared using the Chi-square test, and propensity score matching was performed to determine univariate and multivariate odds ratios of the population regarding a positive vs. negative SARS-CoV-2 result. Results . Of the 121 children, 36 had laboratory-confirmed SARS-CoV-2 infection. The main risk for SARS-CoV-2-associated pediatric hospitalization was contact with a family member with SARS-CoV-2. It was also found that fever and fatigue were statistically significantly associated with a positive SARS-CoV-2 test in multivariate models. Clinical and laboratory data in this Mexican hospitalized pediatric cohort differ from other reports worldwide; the mortality rate (1.6%) of the population studied was higher than that seen in reports from other countries. Conclusion . Our study found that fever and fatigue at hospital presentation as well as an antecedent exposure to a family member with SARS-CoV-2 infection were important risk factors for SARS-CoV-2 positivity in children at hospital admission.